2012
DOI: 10.1021/jp307677b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Functionalized Surface Molecular Monolayers Studied with Ultrafast Infrared Vibrational Spectroscopy

Abstract: The structural dynamics of thin films consisting of tricarbonyl (1,10-phenanthroline)rhenium chloride (RePhen(CO)3Cl) linked to an alkyl silane monolayer through a triazole linker synthesized on silica-on-calcium-fluoride substrates are investigated using ultrafast infrared (IR) techniques. Ultrafast 2D IR vibrational echo experiments and polarization selective heterodyne detected transient grating (HDTG) measurements, as well as polarization dependent FT-IR and AFM experiments are employed to study the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(87 citation statements)
references
References 79 publications
3
84
0
Order By: Relevance
“…In the 2D IR spectra of a similar Re complex measured by Fayer and co-workers, it was observed that spectral inhomogeneity is not sensitive to the chain length of linker groups between the Re complex and the solid surface. 30 Our results demonstrate that the CLSs of HD 2D spectra is an unambiguous way to reveal subtle interactions or dynamics changes when other parameters such as spectral peak positions or linewidths might not be sensitive to the changes because of spectral convolutions.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In the 2D IR spectra of a similar Re complex measured by Fayer and co-workers, it was observed that spectral inhomogeneity is not sensitive to the chain length of linker groups between the Re complex and the solid surface. 30 Our results demonstrate that the CLSs of HD 2D spectra is an unambiguous way to reveal subtle interactions or dynamics changes when other parameters such as spectral peak positions or linewidths might not be sensitive to the changes because of spectral convolutions.…”
mentioning
confidence: 70%
“…We rule out the possibility of intermolecular interactions, since it has been shown in previous studies that the coupling between molecules in a similar Re-complex monolayer is negligible. 30 Among these short range interactions, contributions to homogenous broadening that require the molecules to be chemisorbed on gold surface can be ruled out as well, because the CO modes do not directly attach to the gold surface through either chemi-or physi-adsorptions. These interactions include the non-adiabatic charge transfer interaction 31 and the coupling to low frequency modes, 32,33 such as hindered rotations and translations.…”
mentioning
confidence: 99%
“…16,[49][50][51][52][53] In this case, one molecule is initially excited but subsequently transfers its excitation energy to another oscillator that may have a different transition frequency. Such a mechanism may be particularly relevant in ML samples, where the vibrational probes are fairly close to each other.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable investigations have been performed recently for water at water-air interfaces 51 or metal-carbonyl MLs on silica. 16,50 In the first case, spectral diffusion is dominated by vibrational energy transfer. 51 Conversely, energy-transfer between different molecules in metal-carbonyl MLs was excluded by means of spectral diffusion measurements for chemically diluted samples, i.e., MLs containing a mixture of molecules, only a fraction of which containing the vibrational chromophore.…”
Section: General Context Of Spectral Diffusion At Interfacesmentioning
confidence: 99%
“…For instance, dilution of functional groups on the surface increases the mutual distance between the CN groups and thus results in less favourable condition for, e.g. excitonic coupling 31 or excitation energy transfer 6,32 (EET) between CN groups. The expectation is that the spectral diffusion gets slower in MMLs as compared to MLs if such contributions are eliminated from the underlying dynamics.…”
Section: Resultsmentioning
confidence: 99%